Study of highly excited ro-vibrational states of S18O2 from “hot” transitions: The bands ν1þν2þν3ν2, 2ν1þν2ν2, and 2ν2þν3ν2 O - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Morzhikova Yu. B. Yuliya Borisovna; Maul Christof; Sydow C .; Bauerecker Sigurd (2017, 2017)
Title screen